Can there be an ethics of care?. Issue 1 (February 1995) - Allmark, P
Abstract : There is a growing body of writing, for instance from the nursing profession, espousing an approach to ethics based on care. I suggest that this approach is hopelessly vague and that the vagueness is due to an inadequate analysis of the concept of care. An analysis of 'care' and related terms suggests that care is morally neutral. Caring is not good in itself, but only when it is for the right things and expressed in the right way. 'Caring' ethics assumes wrongly that caring is good, thus it can tell us neither what constitutes those right things, nor what constitutes the right way.